Clinical outcomes after surgical treatment of open thigh muscular tears in skeletally immature patients - Marco Turati; Angelo Mosca; Marco Crippa; Stéphane Tercier; Giulio Leone; Nicolas Nicolaou; Nicolas Bremond; Barbara Kwiatkowski; Aurelien Courvoisier; Marco Bigoni (Journal of Pediatric Orthopaedics B, 2026)
Open thigh muscle lacerations in skeletally immature patients are rare, and evidence on optimal management and outcomes is limited. Among sports, skiing represents a frequent mechanism of injury due to sharp ski edges, yet data on pediatric cases remain scarce. We aimed to describe injury patterns, surgical management, and recovery of pediatric patients with open quadriceps tears. In a retrospective two-center cohort, we included skeletally immature patients with open thigh muscular lacerations treated surgically. Mechanism of injury, contamination status, muscle involvement, and complications were recorded. The Euro Quality of Life 5-Dimension, Pediatric International Knee Documentation Committee (Ped-IKDC), Simple Knee Value (SKV) score, and Tegner Activity score were collected at a minimum 1-year follow-up. Eleven patients (mean age: 13.1 years, range: 7–17) were treated. A total of 73% of the patients experienced a sports-related injury, predominantly sharp ski-edge cuts (55%), and 64% (7/11) presented with contaminated wounds. Vastus lateralis was most frequently involved (55%). One patient presented with an associated sciatic nerve injury. No infections, re-ruptures, or neurovascular sequelae were detected. At the final follow-up, the mean SKV was 93.5%, the mean Pedi-IKDC was 97.6%, and the Euro Quality of Life 5-Dimension 5-Level of Severity was 100%. The return to sport was acceptable with a mean Tegner score of 6.8 (range: 4–9), without reinjuries. Open thigh muscle lacerations in skeletally immature patients – most often related to ski accidents – can be effectively treated with prompt operative exploration, layered repair, short immobilization, and early rehabilitation, resulting in excellent function and full return to sport without reinjury.